Problems of Legal Qualification and Application of Servitudes over Land for Building Use: Problems of Legal Qualification and Application of Servitudes over Land for Building Use - Juzikienė, Renata (Teisė, 2023)
The paper analyses the problems of legal qualification and practical application of servitude over land for building use. The doubts regarding the suitability of the servitude to resolve disputes between different owners of a plot of land and a building on it are raised. The reasonableness of the differences in the scope and compensation calculation of the servitude over land for use of the building determined on different grounds is analysed. Proposals for solving the problems raised in the article are made, the possibility of legal requalification and the legal consequences of it are analysed.